2003
DOI: 10.1143/jpsjs.72sb.99
|View full text |Cite
|
Sign up to set email alerts
|

High Field/High Frequency ESR in Osaka University

Abstract: Recently, a new high field/high frequency ESR system has been developed in KYOKUGEN, Osaka University. The ESR system consists of the far infrared laser and the Gunn oscillator as a light source, and a 70 T pulse magnet. In this paper, the detail of the high field/high frequency ESR system in KYOKUGEN, Osaka University will be described, and the studies on the molecular oxygen, the S=1 dimer compound and the quasi-one-dimensional Ising-like antiferromagnet CsCoCl 3 will be presented as examples of the measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The energy of the excitation is quite close to the anisotropy energy of the natural oxygen in the gas phase reported as 0.5 meV. [27] This suggested that the excitation is due to the single-ion-anisotropy of the adsorbed oxygen molecules.…”
Section: Resultssupporting
confidence: 66%
“…The energy of the excitation is quite close to the anisotropy energy of the natural oxygen in the gas phase reported as 0.5 meV. [27] This suggested that the excitation is due to the single-ion-anisotropy of the adsorbed oxygen molecules.…”
Section: Resultssupporting
confidence: 66%
“…Thus, the adsorbed O 2 molecules will form soft aggregates in the channel. Although the changes of magnetization indicated changes in the magnetic interaction of the O 2 aggregates that were induced by magnetic anisotropy, the energy difference in the change of the configuration of the included O 2 aggregates is too low to be observed under the condition in which the applied magnetic field is low and the temperature of the measurement is high compared with the magnetic anisotropic energy of the O 2 molecules ( D = 5.8 K for the gas phase) . These results suggest that the flexible host stabilizes the configuration of the O 2 aggregates, which enable observation of the states of slightly different energy levels.…”
Section: Resultsmentioning
confidence: 90%
“…The high field ESR measurements are performed using this pulsed magnetic field and FIR laser. 29) Okayama University is a new facility which started in April, 2001. 30) They prepared the 3 He system to perform submillimeter wave ESR down to 0.5 K. They are preparing the submillimeter wave ESR system equipped with the repeated pulsed magnetic field which is a new technique promising for gaining the signal-tonoise ratio in high field ESR measurements.…”
Section: )mentioning
confidence: 99%
“…29 magnetic field, and temperature dependence of the line width in Cu-benzoate, 40) whcih was known but unsolved for a long time. The field and temperature dependences of the line width were clearly interpreted by the (H /T ) 2 behavior obtained by the OA theory.…”
Section: )mentioning
confidence: 99%